Synthesis of modified 1,5-imino-d-xylitols as ligands for lysosomal β-glucocerebrosidase - Zoidl, Manuel (Monatsh Chem, 2019)
ABSTRACT: Modified 1,5-dideoxy-1,5-imino-d-xylitol analogues with different substitution patterns involving position C-1 and/or the ring nitrogen were prepared, which were designed to serve as precursors for the preparation of iminoxylitol-based ligands and tools for the elucidation and modulation of human lysosomal β-glucocerebrosidase. Biological evaluation of the synthesized glycomimetics with a series of glycoside hydrolases revealed that these substitution patterns elicit excellent β-glucosidase selectivities. GRAPHICAL ABSTRACT: [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00706-019-02427-1) contains supplementary material, which is available to authorized users.